Microdomination how to leverage social media and content marketing to build a mini-business empire around your personal brand - Young, Trevor (Gildan Audio, 2020)
Microdomination is based on the premise of building a strong personal brand around what gets you jazzed every day and then growing a sustainable business enterprise around it.The book paints a vivid picture of the possibilities that exist today for someone who has experience and expertise in - and importantly, a passion for - a particular subject, topic, or vocation. This passion could be a professional discipline - i.e., your day job - or a hobby or sideline interest that you're keen to turn into a full-time gig.Part One sets the scene - what constitutes a "Micro Maven," who they are, what their characteristics are. Jam-packed with real-life examples of highly inspirational individuals who are living the dream.Part Two gets more into the nuts and bolts - we dissect what the experts are doing and set about looking at ways and means how you too can replicate what they do to build your platform, your brand, and ultimately your business.